Antibacterial, Antioxidant and Anti-Inflammatory Effect with GCMS Profile of Edible Mushroom Fermented by LAB - Wahid, Jamith Basha Abdul; Aljuwayd, Mohameed; Alruwaili, Muhannad; Nofal, Wesam (International Journal of Pharmaceutical Investigation, 2025)
Background Nutritional modifications arise from an enhanced understanding of the importance of food and its impact on human well-being. Objectives This study investigates the fermentation-based preservation of edible mushrooms using Lactobacillus sp. Methods: The research examines the effects of LAB-mediated fermentation on edible mushrooms and evaluates their bioactive potential. Results The findings indicate that the extract of Agaricus bisporus exhibits superior properties compared to Coriolus versicolor. Nevertheless, both fermented mushrooms displayed significantly lower metal chelating capacity than DPPH radical inhibition efficiency. Agaricus bisporus showed greater antioxidant activity than Calocybe indica, but exhibited lower anti-inflammatory properties. The analyzed LAB effectively fermented Agaricus bisporus, preserving the mushroom and sustaining its biological activity, as evidenced by the identification of more than 30 different volatile compounds through gas chromatography. Conclusion The results suggest that LAB-dependent fermentation of Agaricus bisporus holds promising medicinal value, exhibiting higher antioxidants, antibacterial, and anti-inflammatory properties compared to non-fermented mushrooms. This study highlights the potential of edible mushrooms as sources of antibacterial, antioxidant, and anti-inflammatory compounds, indicating the necessity for further assays to evaluate fermented fungal compounds as safe alternatives to combat antibiotic resistance.
Keywords: Fungi; antioxidant; Lactobacillus; Mushroom; Phenol; DPPH